2012
DOI: 10.3109/02713683.2012.748079
|View full text |Cite
|
Sign up to set email alerts
|

Sealed-capsule Irrigation with Distilled Deionized Water to Prevent Posterior Capsule Opacification – Prospective, Randomized Clinical Trial

Abstract: SCI is a safe procedure and the endothelial cells loss can be associated with the Perfect Capsule™ device (Milvella) in the anterior chamber insertion. DW irrigated for 3' reduces PCO in long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Its osmotic pressure is approximately 0, which is obviously lower than the osmotic pressure of human tissue cells that is within 280 mmol/L∼310 mmol/L, and DW can cause cells bursting by absorbing water to help eliminate cells. Scholars [3,48] infused the capsule with DW for 3 minutes after removing the lens cortex in human cataract surgery and proved that DW could reliably eliminate LECs and decrease the occurrence of lens capsule opacification. For protecting intraocular tissues, Rekas et al…”
Section: Clinical Drugs On Clearing Lecsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its osmotic pressure is approximately 0, which is obviously lower than the osmotic pressure of human tissue cells that is within 280 mmol/L∼310 mmol/L, and DW can cause cells bursting by absorbing water to help eliminate cells. Scholars [3,48] infused the capsule with DW for 3 minutes after removing the lens cortex in human cataract surgery and proved that DW could reliably eliminate LECs and decrease the occurrence of lens capsule opacification. For protecting intraocular tissues, Rekas et al…”
Section: Clinical Drugs On Clearing Lecsmentioning
confidence: 99%
“…Scholars found that LECs include two types, type A and type E LECs. Type A LECs that are located under the anterior capsule have two major functions, EMT and migration towards the equatorial and posterior capsule, whereas equatorial type E LECs with a superior proliferation ability play a critical role in the formation of capsular pearls [3]. In the process of routine operation, most of type A LECs can be eliminated via capsulorhexis, while both type A LECs around the anterior capsule and whole type E LECs hidden by the iris are difficult to remove.…”
Section: Introductionmentioning
confidence: 99%
“…We decided to test two basic substances for PCO prevention, distilled water (H 2 Od) and hydrogen peroxide (H 2 O 2 ). H 2 Od since it has been tested many times before 11 , 13 , 17 , 20 22 and gives us a point of reference with other similar studies, although its effectiveness has been inconsistent. H 2 O 2 was selected due to its known presence in the lens 23 and its dichotomous role in mammalian cells, being harmful or beneficial depending on its location and concentration.…”
Section: Introductionmentioning
confidence: 95%
“…Sealed-capsule irrigation using either distilled water or 5-fluorouracil has been shown to be successful in reducing the incidence of visual axis opacification in adult eyes by killing the LECs. 142 , 143 This device may help pediatric cataract surgeons to overcome the problem of PCO, but the risk of endothelial cell loss cannot be underestimated. The development of the bag-in-the-lens technique by Tassignon et al shows promise, because by using this lens the LECs are trapped between the anterior and posterior capsules, thus reducing dramatically the rate of PCO.…”
Section: Complicationsmentioning
confidence: 99%
“…Capsule-irrigating devices customized for pediatric eyes, which will reduce the speed and severity of proliferation of LECs, or future research discovering the drugs antagonizing the effect of factors responsible for PCO are warranted. 142 , 143 Recently, the results in an animal model indicated that there was a beneficial effect on postoperative inflammation with dexamethasone-coated IOLs. 149 It is reasonable to assume that IOLs will be designed that can deliver slow-release molecules to reduce inflammation and obviate the need for topical anti-inflammatory treatment.…”
Section: Future Directionsmentioning
confidence: 99%